Vad gör en bra park bra? - Bäckström, Josefine; Falk, Mia (2008)
This our bachelor thesis of 15 p ECTS. Our subject is What makes a good park? – And how to make it better. The purpose of our bachelor thesis is to provide an overall direction for instrinsic qualities, resource (areas and materials) maintenance, visitor use, visitor experience and a basic foundation for decision-making for the maintenance and enhancement of the parks in Danderyd municipality.